Introduction to Special Issue on Universal Design for Inclusive Pedagogy and a Future Research Agenda - David R. Arendale (MDPI AG, 2018)
This Special Issue seeks to address the needs of all postsecondary/tertiary students for a barrier-free learning environment to increase their academic achievement, engagement, learning mastery, and persistence to graduation. Universal Design for Inclusive Pedagogy (UDIP) is sensitive to diverse students and individual differences to promote access and equity. While our colleagues in elementary and secondary education have been addressing this issue for many years, postsecondary education is a newer field for this approach. The six articles in this issue break new ground with regards to expanding the boundaries of Universal Design (UD). Areas explored in this Special Issue are transformed curriculum, innovative teaching and learning practices, cross-national and cross-cultural student interactions, application of UD to academic pathways, and UDIP embedded into the institutional culture and policies. The central themes of the articles are increased access, equity, and social justice for all students.